Tax Aggressiveness in Consumer Goods: Liquidity, Leverage, Earnings, and CSR Dynamics: Dinamika Pengaruh Likuiditas, Leverage, Manajemen Laba, dan CSR terhadap Agresivitas Pajak pada Perusahaan Manufaktur Barang Konsumsi - Mutiara Martaningrum; Sriyono Sriyono (Universitas Muhammadiyah Sidoarjo, 2023)
This study explores the relationship between liquidity, leverage, earnings management, corporate social responsibility (CSR), and tax aggressiveness in the consumer goods manufacturing companies listed on the Indonesia Stock Exchange from 2015 to 2019. Employing purposive sampling and panel data regression analysis on secondary data from financial reports, the research aims to assess the individual and combined effects of these factors. The findings reveal that leverage and CSR exhibit a significant negative impact on tax aggressiveness, while liquidity demonstrates a negative effect. Moreover, earnings management is positively associated with tax aggressiveness, albeit not significantly. Simultaneously, the comprehensive analysis reveals that liquidity, leverage, earnings management, and CSR collectively influence tax aggressiveness. These findings provide valuable insights into the interplay between financial and non-financial factors in shaping tax strategies adopted by manufacturing firms, enabling policymakers, practitioners, and scholars to better understand and manage tax behavior in the corporate sector. Highlights: Liquidity and Leverage: The study reveals the negative impact of liquidity and leverage on tax aggressiveness, indicating that companies with higher liquidity and lower leverage tend to exhibit less aggressive tax behavior. Corporate Social Responsibility: The findings demonstrate that corporate social responsibility practices have a significant negative effect on tax aggressiveness, suggesting that socially responsible companies are less likely to engage in aggressive tax strategies. Earnings Management: While not significant, the positive association between earnings management and tax aggressiveness highlights the need for further examination of the complex relationship between financial reporting practices and tax behavior in manufacturing companies. Keywords: Tax Aggressiveness, Liquidity, Leverage, Earnings Management, Manajemen Laba, Corporate Social Responsibility